The Role of Continuing Professional Development (CPD) in Enhancing Teaching Quality: A Systematic Literature Review - Syaharuddin Syaharuddin; Yudin Citriadin; Hazat Usman Mashwani (Universitas Islam DDI A.G.H Abdurrahman Ambo Dalle, 2026)
This study aims to analyze the role of Continuing Professional Development (CPD) in improving the quality of teaching among teachers in schools. The methodology used in this research is a Systematic Literature Review (SLR), with sources of literature selected from Scopus, DOAJ, and Google Scholar, published between 2018 and 2024. The findings of this study indicate that CPD has proven to be effective in enhancing teachers' competencies, students' creativity, and overall teaching quality. However, despite numerous studies showing significant improvements after CPD, challenges such as limited resources, participant engagement, and resistance to change remain major barriers to the success of training programs. Additionally, issues related to infrastructure limitations and access to quality education in underserved areas further contribute to the existing disparities that need greater attention. These findings highlight the importance of developing more inclusive and sustainable training models to address these challenges, ensuring that the outcomes of CPD are maximized and have a broader impact on improving the quality of education.